Exploring the Role of Chatbots in Developing the Virtual Training System from the Trainees' Point of View (The International Journal of Educational Sciences and Arts, 2024)
Chatbots have become the most widely used interactive tools in guiding trainees through electronic training environments. Chatbots enhance trainees' abilities to communicate with training environments. The limited use of chatbots within the Kingdom of Saudi Arabia is one of the guidelines that prompted the researcher to study the role of chatbots in developing the virtual training system from the point of view of the trainees. The study aimed to know the role of chatbots in developing the virtual training system from the point of view of the trainees. A qualitative approach was used, relying on the phenomenological approach as a method of study, based on semi-structured interviews with (12) trainees. The results resulted in identifying the most important roles of chatbots in developing the virtual training system, and this was based around two areas: the role of chatbots in developing the virtual training system from the trainees’ point of view. And the challenges facing trainees in chatbots. The most important challenges were the lack of interaction between the robot and the trainee, which is considered one of the biggest challenges. The difficulty of creating unified groups for general educational use suitable for all needs and groups. The preference for traditional educational methods despite modern technical tools. The lack of experience of trainers and trainees in programming and using robots. Chat, and the need for chat groups to have a protection chat bot to prevent the group from being hacked, as it differs from a bot programmed for content. The research recommended the need to spread a culture of learning and self-training to enhance the role of chat bots in guiding trainees.
Keywords: Chat Robots; Virtual Training; Trainees